2007
DOI: 10.1016/j.anireprosci.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte biology and challenges in developing in vitro maturation systems in the domestic dog

Abstract: The oocyte of the domestic dog is unique from that of other mammalian species studied to date. Ovulation occurs either once or twice per year, with the oocyte released at the germinal vesicle stage and then completing nuclear and cytoplasmic maturation within the oviduct under the influence of rising circulating progesterone. In vivo meiotic maturation of the bitch oocyte is completed within 48 to 72 h after ovulation, which is longer than 12 to 36 h required for oocytes from most other mammalian species. Due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 116 publications
2
66
1
7
Order By: Relevance
“…Since that report, and despite numerous studies documenting and focusing on establishing a suitable system for IVM of canine oocytes [15][16][17][18][19], the efficiency is lower than for other domestic mammalian species, for example cattle [20,21], sheep [22], pigs [23], mice [24], and cats [25]. Although puppies have been produced from somatic cell nuclear transfer of in-vivo matured oocytes [26], there has been no report of the production of live young after transfer of in-vitro maturation and fertilization-derived embryos [27].…”
Section: Introductionmentioning
confidence: 99%
“…Since that report, and despite numerous studies documenting and focusing on establishing a suitable system for IVM of canine oocytes [15][16][17][18][19], the efficiency is lower than for other domestic mammalian species, for example cattle [20,21], sheep [22], pigs [23], mice [24], and cats [25]. Although puppies have been produced from somatic cell nuclear transfer of in-vivo matured oocytes [26], there has been no report of the production of live young after transfer of in-vitro maturation and fertilization-derived embryos [27].…”
Section: Introductionmentioning
confidence: 99%
“…From 1976 (Mahi and Yanagimaci, 1976) to date, numerous studies have been conducted to improve success of in vitro maturation (IVM) of bitch oocytes but an efficient protocol for IVM has not been established. In vitro maturation, generally has resulted in low rates of successful resumption of meiosis, with the exception being one study that found that use of oocytes from follicles larger than 2 mm yielded significantly higher rates of metaphase II development in vitro (Songsasen and Wildt, 2005), where 79.5% of oocytes recovered from follicles 2 mm size reached the second metaphase (MII), usually less than 20% of canine oocytes achieve nuclear maturation (Songsasen and Wildt, 2007). Moreover, only a single blastocyst has been produced after in vitro fertilization of in vitro matured oocytes (Otoi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high specificity of reproductive cycles, the reported symptoms have been somewhat different for various species investigated (Grundy et al 2002, Songsasen and Wildt 2007, Zanghf et al 2007). …”
Section: Discussionmentioning
confidence: 99%